An oxygen heterocycle-fused fluorene based non-fullerene acceptor for high efficiency organic solar cells. (29th June 2020) - Ke, Xin; Meng, Lingxian; Wan, Xiangjian; Sun, Yanna; Guo, Ziqi; Wu, Simin; Zhang, Hongtao; Li, Chenxi; Chen, Yongsheng
Abstract : A new acceptor–donor–acceptor (A–D–A) small molecule acceptor, named FCO-2F, is designed and synthesized based on the previous acceptor F-H. Abstract : A new acceptor–donor–acceptor (A–D–A) small molecule acceptor, named FCO-2F, is designed and synthesized based on the previous acceptor F-H. By inserting an oxygen atom into the backbone of F-H and fluorination on the end group, FCO-2F shows a much red-shifted absorption compared with F-H, and also a wider absorption up to 830 nm. Using polymer PM6 as the donor, the organic solar cell (OSC) devices based on FCO-2F offer a power conversion efficiency (PCE) of 13.36%, with a much improved short circuit current ( J sc ) of 20.90 mA cm −2 .